BUDAYA LENGGER LANANG DALAM FILM KUCUMBU TUBUH INDAHKU KARYA GARIN NUGRAHA DALAM PERSPEKTIF ISLAM - Fajrul Falah; Sayidah Afyatul Masruroh; Anwari; M. Sahrun Ni’am; Ahmad Gunawan Imani (Menara Tebuireng, 2021)
Film is considered as a powerful medium of communication to the masses it targets, because of its audio-visual nature, film is an effective medium for conveying a message. But not all messages can be conveyed properly, therefore it is necessary to formulate the problems in this research: what is the Islamic perspective and hadits prespective on lengger lanang culture contained in the film Kucumbu Body Indahku. To answer the formulation of the problem, the researcher uses a qualitative approach, with the method used is Roland Barthes's Semiotics analysis "Langger Lanang culture in the film Kucumbu Badan Indahku by Garin Nugraha in an Islamic perspective". In this study, Roland Barthes' theory is very relevant for interpreting the sign structure in the film Kissing My Beautiful Body. Roland Barhes classifies significance in two stages, namely denotative meaning and connotative meaning. Roland Barthes also adds myth which is the signifier and the deepest meaning. Then the analysis in this film is focused on lengger lanang culture which includes crossgender and LGBT which is the formulation of the problem in this research. From the results of the meaning of the sign structure contained in the film Kucumbu Berlian Cantikku, there are several scenes about lengger lanang, crossgender, and LGBT. Then these three aspects are analyzed through an Islamic religious perspective with the aim that this research can provide knowledge about crossgender and LGBT that Islam strictly prohibits anyone from doing this and is supported by several arguments in the Qur'an, hadiths, and the opinions of scholars.